Methodology in legal philosophy - Dickson, J (ISTE / Wiley, 2022)
This chapter examines the main issues with regard to correct jurisprudential methodology. The complex and multi-faceted character of law itself hence makes room for pluralism with regard to jurisprudential accounts of it: different theories of law can and do investigate different sets and subsets of those plausibly numerous properties that comprise law's nature, and do so in multiple ways driven by changes in our sense of puzzlement with respect to them. Moreover, given law's involvement in so many important areas of social and political life, philosophy of law engages with and addresses an ever-developing array of questions and puzzles, responding to changing theoretical interests and societal circumstances. The chapter explains a divide in the methodology of legal philosophy between theories of law adopting a directly evaluative methodological approach, and theories of law engaging in indirectly evaluative legal philosophy.